NSDAP YOUTH POLICY: RETROSPECTIVE ANALYSIS (Review of the monograph.: Davletov O. R. Preparation of the “generation of wolves”: training of future perpetrators of the Holocaust (Essays on the youth policy of the NSDAP in 1922 – 1939). 2nd ed., 2019. 316 p.) - Nechaieva-Yuriichuk, Nataliia; Троян, Сергей (Дрогобич: Видавничий дім «Гельветика», 2021)
Review of the monograph.: Davletov O. R. Preparation of the “generation of wolves”: training of future perpetrators of the Holocaust (Essays on the youth policy of the NSDAP in 1922 – 1939). 2nd ed., 2019
МОЛОДІЖНА ПОЛІТИКА НСДАП: РЕТРОСПЕКТИВНИЙ АНАЛІЗ (рецензія на монографію.: Давлєтов О. Р. Підготовка “покоління вовків”: вишкіл майбутніх виконавців Голокосту (Нариси молодіжної політики НСДАП у 1922 – 1939 рр.). 2-е вид. доп. Дніпро: Український інститут вивчення Голокосту “Ткума”, 2019. 316 с.)
Keywords: NSDAP, Youth Policy, World War II, Germany